Validity of automated refraction after segmented refractive multifocal intraocular lens implantation - Albarrán-Diego, César (Int J Ophthalmol, 2017)
AIM: To evaluate the clinical utility of automated refraction (AR) and keratometry (KR) compared with subjective or manifest refraction (MR) after cataract or refractive lens exchange surgery with implantation of Lentis Mplus X (Oculentis GmbH) refractive multifocal intraocular lens (IOL). METHODS: Eighty-six eyes implanted with the Lentis Mplus X multifocal IOL were included. MR was performed in all patients followed by three consecutive AR measurements using the Topcon KR-8000 autorefractor. Assessment of repeatability of consecutive AR before and after dilation with phenylephrine 10%, and comparison of the AR and KR with MR using vector analysis were performed at 3mo follow-up. RESULTS: Analysis showed excellent repeatability of the AR measurements. Linear regression of AR versus MR showed good correlation for sphere and spherical equivalent, whereas the correlation for astigmatism was low. The mean difference AR-MR was -1.28±0.29 diopters (D) for sphere. Astigmatism showed better correlation between KR and MR. CONCLUSION: We suggest AR sphere plus 1.25 D and the KR cylinder as the starting point for MR in eyes with a Lentis Mplus X multifocal IOL. If AR measurements are equal to MR, decentration of the IOL should be suspected.